On the occurrence of a glutaredoxin-like small protein in the anaerobic protozoan parasite Entamoeba histolytica - Birocco, Franco (2023)
Background: Entamoeba histolytica, an intestinal parasitic protozoan that usually lives and multiplies within the human gut, is the causative agent of amoebiasis. To date, de novo glutathione biosynthesis and its associated enzymes have not been identified in the parasite. Cysteine has been proposed to be the main intracellular thiol. Methods: Using bioinformatics tools to search for glutaredoxin homologs in the E. histolytica genome database, we identified a coding sequence for a putative Grx-like small protein (EhGLSP) in the E. histolytica HM-1:IMSS genome. We produced the recombinant protein and performed its biochemical characterization. Results: Through in vitro experiments, we observed that recombinant EhGLSP could bind GSH and L-Cys as ligands. However, the protein exhibited very low GSH-dependent disulfide reductase activity. Interestingly, via UV–Vis spectroscopy and chemical analysis, we detected that recombinant EhGLSP (freshly purified from Escherichia coli cells by IMAC) was isolated together with a redox-labile [Fe[sbnd]S] bio-inorganic complex, suggesting that this protein could have some function linked to the metabolism of this cofactor. Western blotting showed that EhGLSP protein levels were modulated in E. histolytica cells exposed to exogenous oxidative species and metronidazole, suggesting that this protein cooperates with the antioxidant mechanisms of this parasite. Conclusions and general significance: Our findings support the existence of a new metabolic actor in this pathogen. To the best of our knowledge, this is the first report on this protein class in E. histolytica.